2018
DOI: 10.5935/abc.20180248
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Trimetazidine on QT-interval Prolongation and Cardiac Hypertrophy in Diabetic Rats

Abstract: BackgroundTrimetazidine (TMZ) is an anti-ischemic drug. In spite of its protective effects on cardiovascular system, there is no scientific study on the usefulness of TMZ treatment for prolonged QT interval and cardiac hypertrophy induced by diabetes.ObjectivesTo evaluate the effects of TMZ on QT interval prolongation and cardiac hypertrophy in the diabetic rats.MethodsTwenty-four male Sprague-Dawley rats (200-250 g) were randomly assigned into three groups (n = 8) by simple random sampling method. Control (C)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 33 publications
0
13
1
1
Order By: Relevance
“…[ 38 ] Another study of the effects of TMZ in diabetic rats also reported that it significantly reduced IL‐6 levels. [ 39 ] These results appear to be inconsistent with the present study, which may be attributable to our research involving acute ischemia and to TMZ reducing macrophage infiltration. TMZ will probably reduce the levels of IL‐1β, which has a wide spectrum of action from autoimmune diseases to sepsis, by preventing the infiltration of macrophages and through different pathways, such as sirtulin‐1.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…[ 38 ] Another study of the effects of TMZ in diabetic rats also reported that it significantly reduced IL‐6 levels. [ 39 ] These results appear to be inconsistent with the present study, which may be attributable to our research involving acute ischemia and to TMZ reducing macrophage infiltration. TMZ will probably reduce the levels of IL‐1β, which has a wide spectrum of action from autoimmune diseases to sepsis, by preventing the infiltration of macrophages and through different pathways, such as sirtulin‐1.…”
Section: Discussioncontrasting
confidence: 99%
“…The protective effects of TMZ against endothelial dysfunction and inflammation through an increase in microRNA‐24 are also consistent with these findings. [ 39 ] All these results show that TMZ protects the ovarian follicles against apoptosis and inflammation by regulating the NF‐κβ pathway.…”
Section: Discussionmentioning
confidence: 95%
“…Other data supporting ROS participation in this process are that N-acetylcysteine restores total myocardial glutathione, lowers oxidative stress, and reduces myocyte hypertrophy and fibrosis in aortic stenosis rats [ 153 ]. In addition, drugs such as trimetazidine (TZM) decrease cardiac hypertrophy by increasing the level of antioxidant enzymes such as catalase, superoxide dismutase and GSH peroxidase [ 154 ].…”
Section: Role Of Oxidative Stress In the Generation Of Cardiovascular Diseasesmentioning
confidence: 99%
“…9 Além das potenciais estratégias não farmacológicas descritas, novas indicações de medicamentos foram contempladas nos estudos publicados nos ABC. Ramezani-Aliakbari et al 10 avaliaram o uso da trimetazidina em ratos com cardiomiopatia diabética. O fármaco, comumente utilizado para melhorar o metabolismo miocárdico na insuficiência coronariana, reduziu o grau de hipertrofia miocárdica e melhorou parâmetros eletrocardiográficos e de função ventricular.…”
unclassified